Hubungan Dukungan Keluarga Dengan Kepatuhan Kontrol Pasien TB Paru - Ayu Dewi Nastiti; Chandra Kurniawan (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Tuberculosis treatment depends on patient knowledge, socio-economic condition as well as the support of the family. The lack of effort from themselves or the lack of support from family to treatment completely will affect patient obedience to the treatment their follow. The purpose of this research was to determine the relationship of family support with obedience control pulmonary TB in the health center kedundung Magersari Mojokerto city. The research design was analytic cross-sectional correlational approach. Variable research that support family as independent variables and the dependent pulmonary TB control obedience. The population was all patients with pulmonary tuberculosis at the health center visit as many as 41 respondents. Samples colected by concecutive sampling. Data was collected by questionnaires and tested with contingensi coeeficient. The results showed that 18 respondents who have poor family support, there are 18 respondents who are not obedient to followed treatment control. While the 15 respondents who have good family support there are 11 respondents who are obedient to serve treatment control.Based on test data shows the results contingensi coefficient ρ = 0.022, α = 0.05, so that ρ <α then H0 is rejected and H1 accepted that there is a relationship between family support with obedience control treatment of pulmonary tuberculosis in health center Kedundung. This fact shows that families who have a good knowledge and understanding of the importance of their roles and functions in treating pulmonary tuberculosis patients so as to provide good support then pulmonary TB sufferer can comply with the control treatment.Keywords: Family Support, Obedience and Pulmonary Tuberculosis Patients